Logistics: Situating flows in a spatial context. Issue 7 (14th March 2020) - Hesse, Markus
Abstract: The origins of logistics lie in military and imperial methods of expansion and control of geographical space. It is principally associated with the more recent contexts of business management and engineering. Logistics systems are now the conveyor belts of the global system of trade, commerce and production, and its associated techniques and strategies aim at optimizing flows and throughput within discrete units (such as firms), in economic networks and across geographical space. Because flows are important determinants for the development of places, logistics has the power to structure territories. Therefore, it has raised considerable interest in the field of geography, not only with regard to cities and their dense agglomeration of people, buildings, and infrastructure but also in geopolitical terms as it fosters the exploration, control, and surveillance of areas. The paper presents a critical account of logistics operations and their relevance for the making (and unmaking) of territories, related policy dimensions, and future challenges for research.